1995
DOI: 10.1111/j.1365-4362.1995.tb03588.x
|View full text |Cite
|
Sign up to set email alerts
|

Trivial or Terrible? The Psychosocial Impact of Psoriasis

Abstract: Psoriasis does appear to cause significant psychosocial morbidity. Greater awareness by physicians and more comprehensive treatment addressing these psychosocial components may avert, or at least minimize, some of these negative sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 12 publications
5
70
0
7
Order By: Relevance
“…Previous studies have shown that approximately half of the subjects were found to be depressed and anxious with the diagnosis of psoriasis 27 , and that psoriasis patients suffered higher rates of depression and body cathexis problem 28 . In the current study, depression and stress had an impact on psoriasis at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that approximately half of the subjects were found to be depressed and anxious with the diagnosis of psoriasis 27 , and that psoriasis patients suffered higher rates of depression and body cathexis problem 28 . In the current study, depression and stress had an impact on psoriasis at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…4 The inconvenience of phototherapy treatment regimens, the fear of toxic effects on organs with both short-and longterm use of many systemic agents, and the highly visible nature of this disease negatively affect multiple facets of healthrelated quality of life (HRQL). [5][6][7][8][9][10][11] A study by Rapp ture of the impact of this disease, both physically and mentally. There is a significant need for psoriasis therapies not only to reduce the visible symptoms of psoriasis but also to reduce subjective symptoms such as itching, an underrecognized key symptom, [12][13][14][15] and to improve patients' functional status and their physical and emotional well-being.…”
Section: Discussionmentioning
confidence: 99%
“…1 The morbidity associated with psoriasis is well documented in terms of its impact on patients' quality of life. [2][3][4] Many patients experience problems with body image, self-esteem and selfconcept, poor psychological adaptation, and feelings of stigmatization, shame, and embarrassment concerning their appearance. 2,5,6 The disease also places an economic burden on patients, particularly those with severe psoriasis, because they incur out-of-pocket expenses.…”
Section: Soriasis Is a Chronic In-mentioning
confidence: 99%